Value orientations and their importance in enhancing the adaptive opportunities of students – theoretical aspect - Shemyhon, N. (Problems of Engineer-Pedagogical Education, 2021)
The question of the essence and structure of value orientations as well as their influence on the adaptive possibilities of students is considered. It is determined that thanks to the value system there is a whole system of relations between the person, society and the social group that this person belongs to. Values and value orientations play an important role in the formation and development of the personality structure; they influence the general approach to one’s own world, offer the content and focus of one’s social position. Students, as a social group, have both common vital value orientations and special value orientations formed in training, namely, professionally significant value orientations that characterize the human ability to put a value on the activity that they are engaged in. In modern conditions, the value system should contribute to the adaptive qualities of a person in which the personality is capable of being flexible, that is, to rebuild and adapt to the environment, and at the same time maintain their own self. In addition, the value system constitutes the basis for a system of attitudes towards work, professional self-determination, and an individual’s ability to take into account the professional context that they are in and are quickly adapted to. Since valuable relationships are at the heart of the value orientation, the process of adaptation to permanent changes in the labor market should begin with the development of students’ value orientations based on such an instrumental value as the value of permanent self-development, which manifests itself in relevant activities including their ability to learn and retrain throughout life. The analysis made it possible to argue that the formed vocational value orientations of students are one of the most important elements of successful future adaptation to professional activities, since they stimulate their personal professional development, activating the internal mechanisms of the personality (needs, interests, motives, patterns, attitudes); play a strategic role in behavior and activity, determine the areas of professional activities; adjust students’ activities with the help of assessments, orientations and patterns, ensuring the relationship of personal and subject parties of an activity on the basis of personal orientation.